Trade Liberalization and Labor Reform in Latin America and the Caribbean in the 1990s - Gill, Indermit S.; Maloney, William F.; Sanchez-Paramo, Carolina (World Bank, Washington, DC, 2012)
This note synthesizes the findings of research on trade and labor in the region, including World Bank studies on: (i) trade and job quality, (ii) informality, and (iii) labor policies in the region. First, the evidence on the relationship between trade liberalization, macro-restructuring and labor market outcomes during the 1990s is reviewed. Second, labor market rigidities will be analyzed and the extent to which reform efforts facilitated formal employment creation. Finally, based on lessons learned from the 1990s, a new agenda for labor market reform is proposed which reflects more closely the new environment in which Latin American governments now operate.